Estudo Taxonômico das Espécies de Meteoriaceae Kindberg e Brachytheciaceae Schimp, (Bryophyta) na Amazônia Brasileira - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2006)
The family Meteoriaceae Kindberg (moss) consists of 15 to 20 genera and about 300 species, worldwide. For the Neotropical region, 12 genera and 40 species are listed. Recently, some genera and species have been included in the family Brachytheciaceae Schimp, determining the study of this family together with that of Meteoriaceae. In worldwide literature about 30-40 genera and 550 species are mentioned for Brachytheciaceae, while in the Neotropical region about 10 genera and 44 species are cited. The objective of this work is to inventory the species of the Meteoriaceae and Brachyteciaceae families that occur in the Brazilian Amazon region and to conduct taxonomic studies. We analyzed 200 exsiccates deposited in the MG herbarium from several regions such as Amazonas, Rondônia, Tucuruí, Barcarena, Serra dos Carajás, Belém, among others. The results found so far indicate the presence of 5 genera and 7 species, which is much lower than expected. Considering that this work is in progress and that the species deposited in the herbariums of other Amazonian institutions, such as INPA and IAN, still remain to be analyzed, no definitive conclusions can be drawn. However, there is a need for further studies of this group, for the knowledge and exact delimitation of its species in the Amazon.
Taxonomic Study of the Species of Meteoriaceae Kindberg and Brachytheciaceae Schimp, (Bryophyta) in the Brazilian Amazon
Keywords: Meteoriaceae Kindberg; Brachytheciaceae Schimp; Bryophyta; Musgo; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::TAXONOMIA VEGETAL